1960
DOI: 10.1017/s0022029900010499
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed supplements on the yield and composition of milk from cows grazing good pasture

Abstract: SummaryTwo experiments are described in which spring-calved Ayrshire cows were fed supplementary food when grazing good, leafy pasture.In the first experiment 6 lb of a mixture of three parts bruised oats and one part flaked maize was fed daily to three groups of five cows. One group received the supplement from 1 July until 30 October, and the other two groups from 1 August and 1 September respectively. A control group received no supplement.In no month was there any statistical difference in daily milk yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
3

Year Published

1962
1962
1985
1985

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 4 publications
3
6
3
Order By: Relevance
“…Experiments conducted at this Institute with dairy cows at pasture have shown that the feeding of concentrates increased the yield of milk slightly but decreased the profit per cow (2,3). Similar results were reported recently by Wood (10).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Experiments conducted at this Institute with dairy cows at pasture have shown that the feeding of concentrates increased the yield of milk slightly but decreased the profit per cow (2,3). Similar results were reported recently by Wood (10).…”
Section: Introductionsupporting
confidence: 88%
“…Our experiment has also provided additional information on the effect of supplements fed to cows on pasture at a high stocking rate. Previous experiments at this Institute and elsewhere (2,3,10) have shown that increases in milk yield as a result of feeding supplements to cows at pasture were small, but the results were generally obtained in conditions similar to those in treatment (A), the control. The response to the barley feeding in this experiment was better than that found in earlier experiments (2, 3) but it was still small.…”
Section: Discussionmentioning
confidence: 73%
“…The effects of offering hay on milk production were in contrast to the work of Castle et al (1960) and Walsh (1969) who found that hay DM intakes of 1 -4-1-9 kg d"' in spring increased milk fat content but had no effect on milk yield. This reflected the changing partition of nutrients as lactation progressed.…”
Section: Discussioncontrasting
confidence: 86%
“…There were, however, no significant effects on the yield of fat, protein or lactose. The effects of offering hay on milk production were in contrast to the work of Castle et al (1960) and Walsh (1969) who found that hay DM intakes of 1 -4-1-9 kg d"' in spring increased milk fat content but had no effect on milk yield. This probably reflects an increase in fibre intake rather than total DM intake, as the cows in those experiments were offered unrestricted grazing and were relatively low yielding (13-19 kgd"') In this experiment, where cows were higher yielding, both total DM and fibre intake were increased, resulting in increased milk yield and fat production.…”
Section: Discussioncontrasting
confidence: 86%
“…During the grazing season the dairy herd received the minimum amount of supplementary feeding, as experimental work had shown clearly that with good grazing it was uneconomic to feed supplements (4,6). The only concentrates fed were cubes containing calcined magnesite in the first 4 weeks of spring grazing, and a mainly cereal mixture for steaming-up in the autumn.…”
Section: Feedingmentioning
confidence: 99%